The Influence of Customer Value, Product Quality, and Product Attractiveness on Consumer Purchasing Interest in Umkm in Jamu Kampung Kediri City - Pamungkas, Septian Yudha; Ayuanti, Rafikhein Novia (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research tries to find out how these three elements influence consumers' desire to buy in Kampung Jamu, Kediri City (Y), product attractiveness (X2), and consumer buying interest (X3), using a numerical methodology. Eighty-five respondents in Kampung Jamu were sampled using a techniqueAccidental Sampling.SPSS is the analytical software application used, while questionnaires are used for data collection. Various data analysis techniques used include; multiple linear regression analysis, reliability test, partial t test, simultaneous F test, classical assumption test, and coefficient of determination. Customer shopping interest is positively influenced by customer value, as evidenced by the Sig t value of 0.002 < 0.05. Customer buying interest is influenced positively and significantly by product quality, as seen from the Sig value of 0.000 < 0.05. Customer intention to buy a product is positively and significantly correlated with its attractiveness, indicated by a Sig t value of 0.026 < 0.05. Customer value, product attractiveness, and product quality all have an identical influence on customer purchasing intentions, with a Sig t value of 0.000 < 0.05.